Building and toning: An analysis of the institutionalization of mediation in penal matters in Hungary - Fellegi Borbála (Temida)
Since 1 January 2007, victims of crimes and offenders have been offered the chance to have recourse to mediation in Hungary. This paper will first give a short overview of the current situation of mediation in penal matters in Hungary, then it will discuss some general phenomena and dilemmas concerning the general introduction of mediation. After that, I will present a SWOT analysis1 of the current Hungarian mediation system in penal matters. The main goal of this article is to set up certain criteria for the further development of the restorative approach. The lessons we have learnt, the strengths and opportunities of the system and the identification of weaknesses might prove useful for other countries when they choose to introduce mediation, and in relation to the protection of victims in particular.